Groupwork Training for social justice - Woodger, David; Anastacio, Jean (Groupwork, 2013)
This paper examines and analyses experiential groupwork in delivering community and youth work training at Goldsmiths, University of London. The programme has, over its forty year history refined a model of education and training that combines large groupwork and experiential learning. The paper explores our experience of groupwork training. The model developed combines groupwork as a tool for learning and teaching. It is in this arena that students explore and critically reflect on their life and work experiences, and learn to process and articulate their feelings and understandings across a wide range of issues, including democratic social change, equality, identity, empowerment and leadership which all comes from learning how to inwardly reflect and change and develop an awareness of themselves. The paper in particular focuses on the development of students’ identity from which they draw out their learning on equality and sets out that this is central to training for achieving equality and social change.